Implementing the Doha Declaration in OAPI legislation: Do transition periods matter? - Patrick Juvet Lowé Gnintedem (South Centre, 2024)
The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) provided for a number of transition periods allowing countries to engage in a phased implementation of their TRIPS obligations. More specifically, transition periods targeted the patenting of pharmaceutical products. The original deadlines for transition periods have expired for developed and developing country WTO members. However, based on the Doha Declaration on the TRIPS Agreement and Public Health and subsequent TRIPS Council decisions, least developed countries (LDCs) continue to benefit from extended transition periods. In the African Intellectual Property Organization (OAPI), after an amendment in 1999, the legal framework has evolved with the amendment of the Bangui Agreement, i.e., the Act of Bamako of 14 December 2015. As for the previous text, the newly amended Bangui Agreement consecrates the unification on industrial property amongst its seventeen Member States. The main objective of such an amendment remains to adapt its legal framework to the international environment and to the economic and social development needs of Member States. Yet only five OAPI Member States are developing countries; the twelve others are LDCs. Then the question arises: do transition periods consecrated pursuant to the Doha Declaration still matter for LDCs who have agreed to be subjected to the OAPI legislation? This paper points out that transition periods remain relevant in OAPI countries by application of the more favorable rule between the Bangui Agreement and the WTO TRIPS Council decisions. It is however noted that the OAPI current legal framework is still problematic, while its LDCs members are underutilizing this flexibility.
Keywords: 300; TRIPS; Rechtsangleichung; Entwicklungsländer